The Effects of Online Video on Consumers’ Attitudes Toward Local Food - Shuyang Qu; Alexa J Lamm; Joy N Rumble; Ricky W. Telg (Journal of Applied Communications, 2017)
Marketers rate online video as their most utilized content medium. This study used a between-subject control group post-test-only experiment to investigate the effect of three local food messages delivered via online video on U.S. consumers’ attitudes toward local food. The three 30-second videos each featured one of the documented benefits of local food: high quality, support of local economy, and strengthening of social connection. Results indicated all three video treatments yielded a positive attitude toward local food, while respondents in the control group had a neutral attitude. The video treatment featuring local food’s high quality generated a significantly more favorable local food attitude than the other two video treatments. Although the social connection video treatment generated a positive attitude toward local food based on the real limits, it did not significantly differentiate from the control group. Communicators should consider using similar short, online videos for emphasizing the high quality of local food and its support of the local economy to promote local agricultural products. Future research should pair live-action or animated footage with the same messages in the video treatments to identify messages effectiveness. Researchers should also investigate why some individuals respond to local food’s benefit of social connection more readily than the others, and identify strategies to use social connection media frame to promote local food.
Keywords: Local food; framing; online video; national experiment; public attitude